Genome editing in wheat microspores and haploid embryos mediated by delivery of ZFN proteins and cell‐penetrating peptide complexes. Issue 5 (3rd December 2019) - Bilichak, Andriy; Sastry‐Dent, Lakshmi; Sriram, Shreedharan; Simpson, Matthew; Samuel, Pon; Webb, Steve; Jiang, Fengying; Eudes, Francois
Summary: Recent advances in genome engineering technologies based on designed endonucleases (DE) allow specific and predictable alterations in plant genomes to generate value‐added traits in crops of choice. The EXZACT Precision technology, based on zinc finger nucleases (ZFN), has been successfully used in the past for introduction of precise mutations and transgenes to generate novel and desired phenotypes in several crop species. Current methods for delivering ZFNs into plant cells are based on traditional genetic transformation methods that result in stable integration of the nuclease in the genome. Here, we describe for the first time, an alternative ZFN delivery method where plant cells are transfected with ZFN protein that eliminates the need for stable nuclease genomic integration and allows generation of edited, but not transgenic cells or tissues. For this study, we designed ZFNs targeting the wheat IPK1 locus, purified active ZFN protein from bacterial cultures, complexed with cell‐penetrating peptides (CPP) and directly transfected the complex into either wheat microspores or embryos. NGS analysis of ZFN‐treated material showed targeted edits at the IPK1 locus in independent experiments. This is the first description of plant microspore genome editing by a ZFN when delivered as a protein complexed with CPP.